German particle verbs: Compositionality at the syntax-semantics interface - Bott, Stefan; Schulte im Walde, Sabine (Journal of Language Modelling, 2018)
Particle verbs represent a type of multi-word expression composed of a base verb and a particle. The meaning of the particle verb is often, but not always, derived from the meaning of the base verb, sometimes in quite complex ways. In this work, we computationally assess the levels of German particle verb compositionality, with the use of distributional semantic methods. Our results demonstrate that the prediction of particle verb compositionality is possible with statistical significance. Furthermore, we investigate properties of German particle verbs that are relevant for their compositionality: the particular subcategorization behavior of particle verbs and their corresponding base verbs, and the question in how far the verb particles can be attributed meaning by themselves, which they contribute to the particle verb.